PENGELOLAAN POTENSI DESA UNTUK TERCIPTANYA PEMBANGUNAN BERKELANJUTAN BERBASIS TEKNOLOGI DAN SWADAYA MASYARAKAT - Sukadana, I.G.K.; Tenaya, I.G.N.P. (Buletin Udayana Mengabdi; Vol 16 No 3 (2017), 2018)
Increased community participation in the management of technology-based rural potential for the realization of sustainable rural development, is the theme of the program KKN-PPM in the Belok Sidan village. Through how many programs such as: public health programs: the provision of clean water through the application of technology waterwheel pump drive, Application of the gravity method, extension of sanitation, counseling clean and healthy lifestyle. Environmental programs: application of technology absorption wells and biopores yard, greening activities. Production of ground coffee with dryer technology implementation and breaking machine wet coffee. To overcome the problems of the community used several methods, among others: extension methods, methods of assistance, mutual aid methods, methods of application of appropriate technology, and methods of pilot. The results of the implementation of the program: Clean water system with a windmill pump method has been realized. From the results of the evaluation of discharge pumping 0.4 liters per second enough to serve 20 families in Puncak Sari zone. Clean water systems gravity method was finally set at the planning stage results of this activity are detailed engineering design. Clean healthy lifestyle activities has been implemented with the achievement of 150 students from elementary schools 2 Belok/Sidan. Activity Biopori achievements is the rejuvenation biopores 50 and 50 new biopori. Health services around 100 cattle livestock achievements underserved. Greening activities around 1000 trees have been distributed to the public. Business mentoring activities powdered coffee crusher coffee achievements already beoperasi to expectations that the engine rotation of 60 rpm, and dryer system model of the greenhouse. Environmental clean-up activities made five baskets inorganic. Making design cooperative Source Merta Buana is completed.